Downregulation of SIRT1 signaling underlies hepatic autophagy impairment in glycogen storage disease type Ia. - Jun-Ho Cho; Goo-Young Kim; Chi-Jiunn Pan; Javier Anduaga; Eui-Ju Choi; Brian C Mansfield; Janice Y Chou (PLoS Genetics)
A deficiency in glucose-6-phosphatase-α (G6Pase-α) in glycogen storage disease type Ia (GSD-Ia) leads to impaired glucose homeostasis and metabolic manifestations including hepatomegaly caused by increased glycogen and neutral fat accumulation. A recent report showed that G6Pase-α deficiency causes impairment in autophagy, a recycling process important for cellular metabolism. However, the molecular mechanism underlying defective autophagy is unclear. Here we show that in mice, liver-specific knockout of G6Pase-α (L-G6pc-/-) leads to downregulation of sirtuin 1 (SIRT1) signaling that activates autophagy via deacetylation of autophagy-related (ATG) proteins and forkhead box O (FoxO) family of transcriptional factors which transactivate autophagy genes. Consistently, defective autophagy in G6Pase-α-deficient liver is characterized by attenuated expressions of autophagy components, increased acetylation of ATG5 and ATG7, decreased conjugation of ATG5 and ATG12, and reduced autophagic flux. We further show that hepatic G6Pase-α deficiency results in activation of carbohydrate response element-binding protein, a lipogenic transcription factor, increased expression of peroxisome proliferator-activated receptor-γ (PPAR-γ), a lipid regulator, and suppressed expression of PPAR-α, a master regulator of fatty acid β-oxidation, all contributing to hepatic steatosis and downregulation of SIRT1 expression. An adenovirus vector-mediated increase in hepatic SIRT1 expression corrects autophagy defects but does not rectify metabolic abnormalities associated with G6Pase-α deficiency. Importantly, a recombinant adeno-associated virus (rAAV) vector-mediated restoration of hepatic G6Pase-α expression corrects metabolic abnormalities, restores SIRT1-FoxO signaling, and normalizes defective autophagy. Taken together, these data show that hepatic G6Pase-α deficiency-mediated down-regulation of SIRT1 signaling underlies defective hepatic autophagy in GSD-Ia.